2012
DOI: 10.1142/s1084946712500136
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Environment for Entrepreneurship: Evidence From the Developmental States of South Korea and United Arab Emirates

Abstract: The purpose of this research is to examine country institutional profile for encouraging entrepreneurial activity in two developmental states: South Korea and United Arab Emirates. Data was collected from business students in the two countries to examine the favorability of their institutional environment for entrepreneurship. Confirmatory factor analysis indicated high reliability, construct validity and internal consistency for the Korean and Arabic language versions of the questionnaire instrument in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Additionally, they are more successful at accumulating capital once in the United States as compared to Filipino immigrants (Fawcett and Gardner, 1994). A comparative study between Korea and the United Arab Emirates (UAE) found that neither country was very conducive for entrepreneurship (Gupta et al, 2012). Using a country institutional profile by Busenitz et al (2000) to understand the environment for entrepreneurial activity, Korea was found to be lower than the UAE in their overall institutional (policies, rules, laws) availability of entrepreneurship knowledge and skills training, and overall societal attitudes toward entrepreneurship (Busenitz et al, 2000;Gupta et al, 2012).…”
Section: Entrepreneurs In Koreamentioning
confidence: 99%
“…Additionally, they are more successful at accumulating capital once in the United States as compared to Filipino immigrants (Fawcett and Gardner, 1994). A comparative study between Korea and the United Arab Emirates (UAE) found that neither country was very conducive for entrepreneurship (Gupta et al, 2012). Using a country institutional profile by Busenitz et al (2000) to understand the environment for entrepreneurial activity, Korea was found to be lower than the UAE in their overall institutional (policies, rules, laws) availability of entrepreneurship knowledge and skills training, and overall societal attitudes toward entrepreneurship (Busenitz et al, 2000;Gupta et al, 2012).…”
Section: Entrepreneurs In Koreamentioning
confidence: 99%
“…Specifically, they conceived cognitive institutions as "knowledge and skills possessed by the people in a country pertaining to establishing and operating a new business," normative as the extent to "which a country's residents admire entrepreneurial activity and value creative and innovative thinking," and regulatory as encompassing "laws, regulations, and government policies that provide support for new businesses, reduce the risks for individuals starting a new company, and facilitate entrepreneurs' efforts to acquire resources." These three dimensions of the institutional environment have been examined in several countries, such as transitional countries of Eastern Europe , rapidly emerging major economies (REMEs) [Gupta et al, 2014c], and developmental societies [Gupta et al, 2012b].…”
mentioning
confidence: 99%
“…Second, while there has been recognition for some time that institutional factors are tightly linked to an economy's entrepreneurial performance (Busenitz et al, 2000;Spencer and Gomez, 2004;Chiles et al, 2007;Kshetri, 2007;Gupta et al, 2012), little theoretical or empirical work has attempted to specify the exact nature of institutions that lead to an economy's entrepreneurial success. Moreover, while some researchers have examined the effects of institutional environment on entrepreneurial development, they have mainly focussed on the regulatory environment (Manolova et al, 2008).…”
Section: Resultsmentioning
confidence: 99%